Haskell point-free style with no functions in the expression - haskell

I've been trying to take some simple functions and convert them to point-free style for practice.
I started with something like this:
zipSorted x y = (zip . sort) y $ sort x --zipSorted(x, y) = zip(sort(y), sort(x))
and eventually converted it to
zipSorted = flip (zip . sort) . sort
(I'm not sure if this is even the best way to do it but it works)
Now I'm trying to further reduce this expression by not having it depend on zip and sort at all. In other words, I'm looking for this function: (I think its a combinator if my vocabulary isn't mistaken)
P(f, g, x, y) = f(g(y), g(x))
The fact that sort is present twice but only passed in once hinted to me that I should use the applicative functor operator <*> but I can't figure out how for some reason.
From my understanding, (f <*> g)(x) = f(x, g(x)), so I've tried re-writing the first point-free expression in this form:
flip (zip . sort) . sort
(.) (flip $ zip . sort) sort
(flip (.)) sort $ flip (zip . sort)
(flip (.)) sort $ flip $ (zip .) sort
It seems that sort should be x, (flip (.)) should be f, and flip . (zip .) should be g.
p = (flip (.)) <*> (flip . (zip .))
p sort [2, 1, 3] [4, 1, 5]
yields [(1, 1), (4, 2), (5, 3)] as expected, but now I'm lost on how to pull the zip out. I've tried
p = (flip (.)) <*> (flip . (.))
p zip sort [2, 1, 3] [4, 1, 5]
but this doesn't work. Is there a way to convert that expression to a combinator that factors out zip?

Let's start from the beginning:
zipSort x y = zip (sort y) (sort x)
It's slightly weird that it uses its arguments in the opposite order, but we can fix that later with flip.
Here we have a general pattern of a "combining" function of two arguments (here: zip) being passed two values transformed by another function. If we had the same base argument but different transformers, this would have been a liftA2 pattern:
c (f x) (g x)
==
liftA2 c f g x
But here it's the opposite: We have the same transform function on both sides (here: sort), but different arguments (x and y). That's on:
c (f x) (f y)
==
(c `on` f) x y
In your case we get:
zip (sort y) (sort x)
(zip `on` sort) y x
flip (zip `on` sort) x y
So
zipSort = flip (zip `on` sort) -- or: flip (on zip sort)
We can further pull out zip and sort by recognizing the standard two-argument-into-one-argument-function composition:
(\x y -> f (g x y)) == (f .) . g
giving
zipSort = ((flip .) . on) zip sort
Note that this function is less general than the pointful version, however. The original function has type
(Ord a, Ord b) => [a] -> [b] -> [(b, a)]
but the pointfree version has type
(Ord a) => [a] -> [a] -> [(a, a)]
because unifying the two sorts forces them to have the same type.

I just asked lambdabot for the answer, rather than trying to work it out by hand:
<amalloy> #pl \zip sort x y -> (zip . sort) y $ sort x
<lambdabot> join . (((.) . flip) .) . (.)

Related

Haskell dot operator with sort and (++) [duplicate]

This question already has answers here:
Haskell function composition operator of type (c→d) → (a→b→c) → (a→b→d)
(6 answers)
Closed last year.
I am learning haskell at the moment and trying to figure out all the rules of prefix, infix, precedence, etc.
While trying to implement a function which appends two lists and sorts them I started with:
appendAndSort :: [a] -> [a] -> [a]
appendAndSort = sort . (++)
which does no compile.
Following:
appendAndSort :: Ord a => [a] -> [a] -> [a]
appendAndSort = (sort .) . (++)
on the other hand does work.
Why do I have to add a second dot at sort and parentheses around it?
Let's start with a version that uses explicit parameters.
appendAndSort x y = sort (x ++ y)
Writing ++ as a prefix function rather than an operator yields
appendAndSort x y = sort ((++) x y)
Knowing that (f . g) x == f (g x), we can identify f == sort and g == (++) x to get
appendAndSort x y = (sort . (++) x) y
which lets us drop y as an explicit parameter via eta conversion:
appendAndSort x = sort . (++) x
The next step is to repeat the process above, this time with (.) as the top most operator to write as a prefix function,
appendAndSort x = (.) sort ((++) x)
then apply the definition of . again with f == (.) sort and g == (++):
appendAndSort x = (((.) sort) . (++)) x
and eliminate x via eta conversion
appendAndSort = ((.) sort) . (++)
The last step is to write (.) sort as an operator section, and we're done with our derivation.
appendAndSort = (sort .) . (++)
The expression (f . g) x means f (g x).
Coherently, (f . g) x y means f (g x) y.
Note how y is passed as a second parameter to f, not to g. The result is not f (g x y).
In your case, (sort . (++)) x y would mean sort ((++) x) y, which would call sort with first argument (++) x (the function which prepends the list x to its list argument), and with second argument y. Alas, this is ill-typed since sort only takes one argument.
Consequently, this is also invalid
appendAndSort x y = (sort . (++)) x y
hence so is this
appendAndSort = sort . (++)
By contrast, ((f .) . g) x y does work as expected. Let's compute:
((f .) . g) x y
= -- same reasoning as above, y is passed to (f.), not g
(f .) (g x) y
= -- application associates on the left
((f .) (g x)) y
= -- definition of `(f.)`
(f . (g x)) y
= -- definition of .
f ((g x) y)
= -- application associates on the left
f (g x y)
So this really makes y to be passed to g (and not f).
In my opinion the "idiom" (f .) . g isn't worth using. The pointful \x y -> f (g x y) is much simpler to read, and not terribly longer.
If you really want, you can define a custom composition operator to handle the two-argument case.
(.:) f g = \x y -> f (g x y)
Then, you can write
appendAndSort = sort .: (++)

make function with 'if' point-free

I have a task in Haskell (no, it's not my homework, I'm learning for exam).
The task is:
Write point-free function numocc which counts occurrences of element in given lists. For example: numocc 1 [[1, 2], [2, 3, 2, 1, 1], [3]] = [1, 2, 0]
This is my code:
addif :: Eq a => a -> Int -> a -> Int
addif x acc y = if x == y then acc+1 else acc
count :: Eq a => a -> [a] -> Int
count = flip foldl 0 . addif
numocc :: Eq a => a -> [[a]] -> [Int]
numocc = map . count
numocc and count are 'point-free', but they are using function addif which isn't.
I have no idea how can I do the function addif point-free. Is there any way to do if statement point-free? Maybe there is a trick which use no if?
I would use the fact that you can easily convert a Bool to an Int using fromEnum:
addif x acc y = acc + fromEnum (x == y)
Now you can start applying the usual tricks to make it point-free
-- Go prefix and use $
addif x acc y = (+) acc $ fromEnum $ (==) x y
-- Swap $ for . when dropping the last argument
addif x acc = (+) acc . fromEnum . (==) x
And so on. I won't take away all the fun of making it point free, especially when there's tools to do it for you.
Alternatively, you could write a function like
count x = sum . map (fromEnum . (==) x)
Which is almost point free, and there are tricks that get you closer, although they get pretty nasty quickly:
count = fmap fmap fmap sum map . fmap fmap fmap fromEnum (==)
Here I think it actually looks nicer to use fmap instead of (.), although you could replace every fmap with (.) and it would be the exact same code. Essentially, the (fmap fmap fmap) composes a single argument and a two argument function together, if you instead give it the name .: you could write this as
count = (sum .: map) . (fromEnum .: (==))
Broken down:
> :t fmap fmap fmap sum map
Num a => (a -> b) -> [a] -> b
So it takes a function from b to a numeric a, a list of bs, and returns an a, not too bad.
> :t fmap fmap fmap fromEnum (==)
Eq a => a -> a -> Int
And this type can be written as Eq a => a -> (a -> Int), which is an important thing to note. That makes this function's return type match the input to fmap fmap fmap sum map with b ~ Int, so we can compose them to get a function of type Eq a => a -> [a] -> Int.
why not
numocc x
= map (length . filter (== x))
= map ((length .) (filter (== x)) )
= map (((length .) . filter) (== x))
= map (((length .) . filter) ((==) x))
= map (((length .) . filter . (==)) x)
= (map . ((length .) . filter . (==))) x
= (map . (length .) . filter . (==)) x
and then the trivial eta-contraction.
One trick would be to import one of the many if functions, e.g. Data.Bool.bool 1 0 (also found in Data.Bool.Extras).
A more arcane trick would be to use Foreign.Marshal.Utils.fromBool, which does exactly what you need here. Or the same thing, less arcane: fromEnum (thanks #bheklilr).
But I think the simplest trick would be to simply avoid counting yourself, and just apply the standard length function after filtering for the number.
Using the Enum instance for Bool, it is possible to build a pointfree replacement for if that can be used in more general cases:
chk :: Bool -> (a,a) -> a
chk = ([snd,fst]!!) . fromEnum
Using chk we can define a different version of addIf:
addIf' :: Eq a => a -> a -> Int -> Int
addIf' = curry (flip chk ((+1),id) . uncurry (==))
Now we can simply replace chk in addIf':
addIf :: Eq a => a -> a -> Int -> Int
addIf = curry (flip (([snd,fst]!!) . fromEnum) ((+1),id) . uncurry (==))
I think you’re looking for Data.Bool’s bool, which exists since 4.7.0.0 (2014–04–08).
incif :: (Eq a, Enum counter) => a -> a -> counter -> counter
incif = ((bool id succ) .) . (==)
The additional . allows == to take two parameters, before passing the expression to bool.
Since the order of parameters is different, you need to use incif like this:
(flip . incif)
(Integrating that into incif is left as an exercise to the reader. [Translation: It’s not trivial, and I don’t yet know how. ;])
Remember that in Haskell list comprehensions, if conditionals can be used in the result clause or at the end. But, most importantly, guards without if can be used to filter results. I am using pairs from zip. The second of the pair is the list number. It stays constant while the elements of the list are being compared to the constant (k).
Your result [1,2,0] does not include list numbers 1, 2 or 3 because it is obvious from the positions of the sums in the result list. The result here does not add the occurrences in each list but list them for each list.
nocc k ls = [ z | (y,z) <- zip ls [1..length ls], x <- y, k == x]
nocc 1 [[1, 2], [2, 3, 2, 1, 1], [3]]
[1,2,2] -- read as [1,2,0] or 1 in list 1, 2 in list 2 and 0 in list 3

Point-free equivalent

I have this function from another SO question,
f :: Ord a => [a] -> [(a, Int)]
f xs = zipWith (\x ys -> (x, length $ filter (< x) ys)) xs (inits xs)
I'm trying to write it in point-free style,
f = flip (zipWith (\x -> (,) x . length . filter (< x))) =<< inits
Is it possible to get rid of that x ?
It's possible, but absolutely not worth the pain. To directly answer your question, LambdaBot on FreeNode reports:
f = flip (zipWith (liftM2 (.) (,) ((length .) . filter . flip (<)))) =<< inits
At this point the function has lost whatever clarity it had, and has become unmaintainable. Here you'd do much better to introduce real names. Remember, just because we can make things point free does not mean we should.
As a general rule: if a variable turns up more than once in an expression, it's probably not a good idea to make it point-free. If you're determined however, the least unreadable way is with the Arrow combinators, because that makes it pretty clear where the data flow is "split". For the xs I'd write
uncurry (zipWith (...)) . (id &&& inits)
For x, the same method yields
zipWith ( curry $ uncurry(,) . (fst &&& length . uncurry filter . first(>)) )
This is even longer than the (->)-monad solution that you've used and lambdabot suggests, but it looks far more organised.
The point of pointfree style is not just omitting names for values, but preferring names for functions. This is significantly easier to do when you use very small definitions. Of course any code is going to become unreadable if you inline everything and don’t use good names.
So let’s start with your original function, and split it into a few smaller definitions.
f xs = zipWith combine xs (inits xs)
combine x xs = (x, countWhere (< x) xs)
countWhere f xs = length (filter f xs)
Now we can easily make these definitions pointfree in a readable way.
f = zipWith combine <*> inits
where combine = compose (,) countLessThan
compose = liftA2 (.)
countLessThan = countWhere . flip (<)
countWhere = length .: filter
(.:) = (.) . (.)
Using names judiciously and preferring composition over application allows us to factor code into small, easily understood definitions. Named parameters are the equivalent of goto for data—powerful, but best used to build reusable higher-level structures that are easier to understand and use correctly. These compositional combinators such as (.) and <*> are to data flow what map, filter, and fold are to control flow.
My stab at it:
f :: Ord a => [a] -> [(a, Int)]
f = zip <*> ((zipWith $ (length .) . filter . (>)) <*> inits)
Here I replaced (<) with (>) to have (length .) . filter . (>) as a function with arguments in the right order: a->[a]->Int. Passing it to zipWith, we get [a]->[[a]]->[Int].
Assuming we have [a] on input, we can see this as f ([[a]]->[Int]) for Applicative ((->) [a]), which can be combined with inits :: f [[a]] with <*> :: f ([[a]]->[Int])->f [[a]]->f [Int]. This gives us [a]->[Int], now need to consume both [a] and [Int] in parallel. zip is already of the right type: [a]->[Int]->[(a,Int)] to apply with <*>.
Not saying I recommend this, but the King of Pointfree is Control.Arrow
import Control.Arrow
-- A special version of zipWith' more amenable to pointfree style
zipWith' :: ((a, b) -> c) -> ([a], [b]) -> [c]
zipWith' = uncurry . zipWith . curry
f :: Ord a => [a] -> [(a, Int)]
f = zipWith' (fst &&& (length <<< uncurry filter <<< first (>))) <<< id &&& inits
Let me reclarify here—I really don't recommend this unless your intention is to somehow generalize the kind of arrow your program is operating in (e.g. into Arrowized FRP perhaps).
With the well-known
(f .: g) x y = f (g x y)
it is a semi-readable
zipWith (curry (fst &&& uncurry (length .: (filter . flip (<))) )) <*> inits
-- \(x,ys) -> (x , length ( (filter . flip (<)) x ys) )
Using Control.Applicative (f <*> g $ x = f x (g x), the S combinator), and Control.Arrow (as others, but a little bit differently).

Understanding function composition with negate

After reading through a page on Higher Order Functions from an awesome site I am still having trouble understanding the negate function paired with function composition.
to be more specific, take this piece of code:
ghci> map (negate . sum . tail) [[1..5],[3..6],[1..7]]
which yields:
[-14,-15,-27]
I re-read the page again, but to be honest, I still have no idea how that line of code produced this answer, if someone could walk me through the process of this I would really appreciate it!
map f [a,b,c] = [f a, f b, f c]
because map f (x:xs) = f x:map f xs - apply f to each element of the list.
So
map (negate.sum.tail) [[1..5],[3..6],[1..7]]
= [(negate.sum.tail) [1..5], (negate.sum.tail) [3..6], (negate.sum.tail) [1..7]]
now
(negate . sum . tail) [1..5]
= negate (sum (tail [1,2,3,4,5]))
= negate (sum [2,3,4,5])
= negate 14
= -14
because (f.g) x = f (g x) and . is right associative, so (negate.sum.tail) xs = (negate.(sum.tail)) xs which in turn is negate ((sum.tail) xs) = negate (sum (tail xs)).
tail gives you everything except the first element of a list: tail (x:xs) = xs, for example tail "Hello" = "ello"
sum adds them up as you expect, and
negate x = -x.
The others work similarly, giving minus the sum of the tail of each list.
To add a different perspective to AndrewC's excellent answer I usually think about these types of problems in terms of the functor laws and fmap. Since map can be thought of as a specialization of fmap to lists we can replace map with the more general fmap and keep the same functionality:
ghci> fmap (negate . sum . tail) [[1..5],[3..6],[1..7]]
Now we can apply the composition functor law using algebraic substitution to shift where the composition is happening and then map each function individually over the list:
fmap (f . g) == fmap f . fmap g -- Composition functor law
fmap (negate . sum . tail) $ [[1..5],[3..6],[1..7]]
== fmap negate . fmap (sum . tail) $ [[1..5],[3..6],[1..7]]
== fmap negate . fmap sum . fmap tail $ [[1..5],[3..6],[1..7]]
== fmap negate . fmap sum $ fmap tail [[1..5],[3..6],[1..7]]
== fmap negate . fmap sum $ [tail [1..5],tail [3..6],tail [1..7]] -- As per AndrewC's explanation
== fmap negate . fmap sum $ [[2..5],[4..6],[2..7]]
== fmap negate $ [14, 15, 27]
== [-14, -15, -27]

How do I re-write a Haskell function of two argument to point-free style

I have the following function in Haskell
agreeLen :: (Eq a) => [a] -> [a] -> Int
agreeLen x y = length $ takeWhile (\(a,b) -> a == b) (zip x y)
I'm trying to learn how to write 'idiomatic' Haskell, which seem to prefer using . and $ instead of parenthesis, and also to prefer pointfree code where possible. I just can't seem to get rid of mentioning x and y explicitly. Any ideas?
I think I'd have the same issue with pointfreeing any function of two arguments.
BTW, this is just in pursuit of writing good code; not some "use whatever it takes to make it pointfree" homework exercise.
Thanks.
(Added comment)
Thanks for the answers. You've convinced me this function doesn't benefit from pointfree. And you've also given me some great examples for practicing transforming expressions. It's still difficult for me, and they seem to be as essential to Haskell as pointers are to C.
and also to prefer pointfree code where possible.
Not "where possible", but "where it improves readability (or has other manifest advantages)".
To point-free your
agreeLen x y = length $ takeWhile (\(a,b) -> a == b) (zip x y)
A first step would be to move the ($) right, and replace the one you have with a (.):
agreeLen x y = length . takeWhile (\(a,b) -> a == b) $ zip x y
Now, you can move it even further right:
agreeLen x y = length . takeWhile (uncurry (==)) . zip x $ y
and there you can immediately chop off one argument,
agreeLen x = length . takeWhile (uncurry (==)) . zip x
Then you can rewrite that as a prefix application of the composition operator,
agreeLen x = (.) (length . takeWhile (uncurry (==))) (zip x)
and you can write
f (g x)
as
f . g $ x
generally, here with
f = (.) (length . takeWhile (uncurry (==)))
and g = zip, giving
agreeLen x = ((.) (length . takeWhile (uncurry (==)))) . zip $ x
from which the argument x is easily removed. Then you can transform the prefix application of (.) into a section and get
agreeLen = ((length . takeWhile (uncurry (==))) .) . zip
But, that is less readable than the original, so I don't recommend doing that except for practicing the transformation of expressions into point-free style.
You could also use:
agreeLen :: (Eq a) => [a] -> [a] -> Int
agreeLen x y = length $ takeWhile id $ zipWith (==) x y
Idiomatic Haskell is whatever is easier to read, not necessarily what is most point-free.
As pointed out in Daniel's excellent answer, your problem is to compose f and g when f as one argument and g two. this could be written f ??? g with the correct operator (and with a type signature of (c -> d) -> (a -> b -> c) -> a -> b -> d.
This correspond to the (.).(.) operator (see there) which is sometimes defines as .:. In that case your expression becomes
length . takeWhile (uncurry (==)) .: zip
If you are used to the .: operator, then this point free version is perfectly readable. I can also instead use (<$$$>) = fmap fmap fmap and get
length . takeWhile (uncurry (==)) <$$$> zip
Another concise, point-free solution:
agreeLen = ((length . takeWhile id) .) . zipWith (==)
Equivalently:
agreeLen = (.) (length . takeWhile id) . zipWith (==)

Resources